Upregulation of HSPA1A/HSPA1B/HSPA7 and Downregulation of HSPA9 Were Related to Poor Survival in Colon Cancer - Guan, Yufeng; Zhu, Xianjun; Liang, Junjie; Wei, Min; Huang, Shan; Pan, Xiaofen (Frontiers in Oncology, 2021)
The human HSP70 family is a member of the heat shock proteins (HSPs), consisting of 13 members encoded by the HSPA genes. HSPs play important roles in regulating cellular responses and functions during carcinogenesis, but the relationship with colon cancer is unclear. In our study, we found that the expression of HSPA1B, HSPA4, HSPA5, HSPA6, HSPA8, HSPA9, HSPA13and HSPA14 were significantly increased while HSPA1A, HSPA2, HSPA7 and HSPA12B were significantly decreased in colon cancer tissues. Expression of HSPA gene family members was associated with some clinicopathological characteristics, including age, gender, TNM stage, pathological stage and CEA level. Furthermore, Kaplan-Meier method and cox regression analysis showed that high HSPA1A, HSPA1B and HSPA7 expression were related to unfavorable survival and high HSPA9 was associated with favorable survival. The relationship between HSPA1A and HSPA9 expression and survival was validated in GEO dataset and the HSPA1A and HSPA9 protein expression difference between colon cancer tissues and normal tissues was validated in UALCAN database. Methylation of HSPA1A and HSPA9 were also analyzed and it was found that the methylation of HSPA1A promoter was significantly increased and methylation of HSPA9 promoter was significantly decreased in colon cancer tissues. Increasing methylation level of HSPA1A gene and decreasing methylation level of HSPA9 were related to favor prognosis. The expression difference of HSPA1A/HSPA1B/HSPA7/HSPA9 were verified in colon cancer cell lines and colonic epithelial cells. Gene ontology analysis was used to screened signal pathways related to HSPA1A-, HSPA1B-, HSPA7- and HSPA9- high phenotype. In summary, the increased expression of HSPA1A1, HSPA1B and HSPA7 was associated with poor prognosis while HSPA9 was related to favor prognosis for colon cancer patients.